Continued spring phenological advance under global warming hiatus over the Pan-Third Pole - Yan, Zhengjie; Xu, Jinfeng; Wang, Xiaoyi; Yang, Zhiyong; Liu, Dan; Li, Guoshuai; Huang, Huabing (Frontiers in Plant Science, 2022)
The global surface temperature has witnessed a warming hiatus in the first decade of this century, but how this slowing down of warming will impact spring phenology over Pan-Third Pole remains unclear. Here, we combined multiple satellite-derived vegetation indices with eddy covariance datasets to evaluate the spatiotemporal changes in spring phenological changes over the Pan-Third Pole. We found that the spring phenology over Pan-Third Pole continues to advance at the rate of 4.8 days decade-1 during the warming hiatus period, which is contrasted to a non-significant change over the northern hemisphere. Such a significant and continued advance in spring phenology was mainly attributed to an increase in preseason minimum temperature and water availability. Moreover, there is an increasing importance of precipitation on changes in spring phenology in the last four decades, and this increasingly negative correlation was also found across more than two-thirds of the dryland region, tentatively suggesting that spring phenological changes might shift from temperature to precipitation-controlled over the Pan-Third Pole in a warmer world.